Salix subserrata bark extract-loaded chitosan nanoparticles attenuate neurotoxicity induced by sodium arsenate in rats in relation with HPLC-PDA-ESI-MS/MS profile - Hamdan, Dalia; Tawfeek, Nora; El-Shiekh, Riham A.; Khalil, Heba M. A.; Mahmoud, Mohamed Y.; Bakr, Alaa F.; Zaafar, Dalia; Farrag, Nawaal; Wink, Michael; El-Shazly, Assem Mohamed (AAPS PharmSciTech, 2022)
Pollution is a worldwide environmental risk. Arsenic (As) is an environmental pollutant with a major health concern due to its toxic effects on multiple body organs, including the brain. Humans are exposed to As through eating contaminated food and water or via skin contact. Salix species (willow) are plants with medicinal efficacy. Salix subserrata Willd bark extract-loaded chitosan nanoparticles (SBE.CNPs) was formulated, characterized, and evaluated against As-induced neurotoxicity. The stem bark was selected for nanoparticle formulation based on HPLC-PDA-ESI-MS/MS profiling and in vitro antioxidant assessment using free radical scavenging activity. SBE.CNPs demonstrated an average un-hydrated diameter of 193.4 ± 24.5 nm and zeta potential of + 39.6 ± 0.4 mV with an encapsulation efficiency of 83.7 ± 4.3%. Compared to As-intoxicated rats, SBE.CNP-treated rats exhibited anxiolytic activity and memory-boosting as evidenced in open field test, light-dark activity box, and Y-maze. Also, it increased the antioxidant biomarkers, including superoxide dismutase and glutathione peroxidase associated with reducing the malondialdehyde levels and apoptotic activity. Besides this, SBE.CNPs maintained the brain architecture and downregulated both nuclear factor-kappa B and heme oxygenase-1 expression. These results suggest that SBE.CNP administration showed promising potent neuroprotective and antioxidative efficiencies against arsenic-induced oxidative threats.
Gesehen am 31.01.2023